Hydropower and Eco-Based Communities: Balancing Renewable Energy Development with Socioeconomic and Environmental Resilience in Developing Nations - Sharma, Samjhana Rawat; Sharma, Manan (Journal of Sustainability and Environmental Management, 2025)
Hydropower projects are a cornerstone of renewable energy development, offering significant contributions to global energy demands while posing socioeconomic and environmental challenges. In developing countries, these projects have profound impacts on eco-based communities, influencing livelihoods, income, infrastructure development, and access to essential services such as education and healthcare. However, they also raise concerns about displacement, biodiversity loss, water quality, and climate resilience. This study comprehensively examines the multifaceted impacts of hydropower projects on eco-based communities in developing countries. Drawing on case studies from Asia, Africa, and South America, the research highlights the challenges of resettlement, environmental degradation, and governance while proposing strategies for sustainable development. Recommendations include rigorous environmental assessments, adaptive management practices, equitable benefit-sharing mechanisms, and enhanced stakeholder engagement. By balancing the dual imperatives of renewable energy and environmental preservation, hydropower projects can play a pivotal role in advancing sustainable development in resource-constrained regions.